Digital Manipulation: Self-Presentation in the Film The Tinder Swindler - Fernandez, Maria Angela; Rahmanto, Andre Noevi; Pawito (International Journal of Media and Communication Research, 2025)
The development of digital technology, including social media, has emerged as a means of communicating with other people, one of which is the dating application called Tinder. Socializing, doing work, dating, and sharing life stories on social media are examples of daily activities carried out by people around the world. The focus of this research is on identity manipulation techniques which are studied using self-presentation strategy theory by Erving Goffman. This study describes how the main character uses digital platforms to manipulate using the Tinder application, as documented in the documentary film "The Tinder Swindler", resulting in losses and heartbreak felt by the victims of the dating application. The purpose of this research is to look at the digital manipulation carried out by the main character who uses the Tinder application through deceptive self-presentation for personal gain and to analyze the self-presentation strategies used in these acts of manipulation. This research methodology is qualitative using a content analysis approach which is used to explore the manipulative strategies carried out by the main character. Therefore, the results of this study show that by utilizing dating applications such as Tinder, social media, and other communication technologies, a person is able to create a very convincing fake identity and use various self-presentation strategies to deceive many victims and get everything they need through the media social.